ANALISIS FAKTOR YANG MEMPENGARUHI INVESTASI ASING LANGSUNG DI INDONESIA PADA TAHUN 1989 - 2019 - Elis Laili Khoirun Nisa’; Whinarko Juliprijanto (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This research aims to find out the relationship between GDP, Labor, Exports and Exchange Rates to foreign direct investment in Indonesia from 1986 to 2019. Using time series data, data analysis techniques use the Error Correction Model (ECM) model, which is then followed by Eviews 10. The results of the analysis showed that the long-term calculation of GDP variables was not significant but had a positive effect, exports had a significant effect, while labor and exchange rates had a negative and insignificant effect. Furthermore, the results of short-term analysis, GDP and Exchange Rate variables are insignificant and negative value, while for Export and Labor variables are insignificant and positive value.